KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL PEMEDIASI PADA HUBUNGAN KEPUASAN KERJA DENGAN KINERJA: PENDEKATAN MODEL TIGA KOMPONEN - Ratno Purnomo; Ratni Zulaikha (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2007)
This study examined the mediating effects of organizational commitments on the relationship between job satisfaction and job performance. It also examined the effect of job satisfaction on organizational commitment, the effect of organizational commitment on job performance and the direct effect of job satisfaction on job performance.Respondents were the nurses of a private hospital located in Yogyakarta (N = 151). Using hierarchical regression analysis, there are three main findings. First, organizational commitment had no mediating effect on the relationship between job satisfaction and job performance. Second, job satisfaction had an effect to organizational commitment. Third, organizational commitment had no effect on job performance and job satisfaction had a direct effect on job performance. Implications for future research and practice are discussed.